2022
DOI: 10.3389/fnut.2022.802940
|View full text |Cite
|
Sign up to set email alerts
|

How a 7-Week Food Literacy Cooking Program Affects Cooking Confidence and Mental Health: Findings of a Quasi-Experimental Controlled Intervention Trial

Abstract: Obesity and mental health disorders are rising simultaneously with shifting dietary behavior away from home cooking, toward typically nutrition-poor and energy-dense convenience meals. Food literacy strongly influences nutrition choices. Community-based cooking interventions target barriers to healthy eating and facilitate development of food literacy skills, thereby potentially increasing preparation of home-cooked meals and positively influencing health. This study of 657 healthy Australian adults explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 103 publications
(168 reference statements)
1
15
0
Order By: Relevance
“…These findings align with previous literature showing that nutrition education and cooking programs can improve nutrition-related skills and knowledge in various populations [ 33 , 34 , 35 ]. While previous research focusing explicitly on FL has been promising regarding the effectiveness of interventions on FL in diverse adult populations [ 27 , 38 , 39 ], our findings strengthen the evidence by focusing on OWs as a population with an increased risk of chronic disease [ 8 ]. Establishing FL as a variable that can be improved through health promotion interventions is vital because research on the closely related and more extensively studied concept of health literacy states that health literacy can be viewed as an asset that empowers individuals to exert greater control over their health [ 65 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings align with previous literature showing that nutrition education and cooking programs can improve nutrition-related skills and knowledge in various populations [ 33 , 34 , 35 ]. While previous research focusing explicitly on FL has been promising regarding the effectiveness of interventions on FL in diverse adult populations [ 27 , 38 , 39 ], our findings strengthen the evidence by focusing on OWs as a population with an increased risk of chronic disease [ 8 ]. Establishing FL as a variable that can be improved through health promotion interventions is vital because research on the closely related and more extensively studied concept of health literacy states that health literacy can be viewed as an asset that empowers individuals to exert greater control over their health [ 65 ].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, a four-week online FL program targeting Australian adults improved FL and increased fruit and vegetable consumption [ 38 ]. However, a study by Rees et al [ 39 ] on participants of a seven-week cooking program showed increased cooking confidence, but yielded no improvements in nutrition knowledge or healthy eating.…”
Section: Introductionmentioning
confidence: 99%
“…Reicks et al conducted a systematic review of 28 research studies and found that cooking interventions led to positive changes in health status and improved intake of fiber, fat, and sodium, which have all been associated with the onset of chronic disease [ 9 ]. Adhering to a diet that follows the dietary guidelines is pivotal to decreasing overweight and obesity rates, and reducing the risk of chronic diseases such as cardiovascular disease and cancer [ 10 ]. The benefits of cooking at home go beyond the improvement of health status.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a fourweek online FL program targeting Australian adults improved FL and increased fruit and vegetable consumption [37]. However, a study by Rees et al [38] on participants of a sevenweek cooking program showed increased cooking confidence but yielded no improvements in nutrition knowledge or healthy eating.…”
Section: Current State Of the Research On Food Literacymentioning
confidence: 98%
“…Considering these extensive sociocultural nutrition-36 related threats to the health of individuals and societies, enabling people to make healthier 37 food choices to prevent chronic disease is a key challenge in the modern world [1,6]. 38 A large part of the population for which specific nutrition-related health threats have 39 been investigated are office workers, who represent about 37% of all employees in commitment, lack of time, and cost of food [9][10][11][12]. Together, these barriers shape a challenging environment for maintaining a healthy diet in the workplace.…”
Section: Introductionmentioning
confidence: 99%